A Ligand That Targets CUG Trinucleotide Repeats. Issue 42 (25th August 2016) - Li, Jinxing; Matsumoto, Jun; Bai, Li‐Ping; Murata, Asako; Dohno, Chikara; Nakatani, Kazuhiko
Abstract: Invited for the cover of this issue is the group of Kazuhiko Nakatani at the Osaka University. The image depicts the novel molecule DAP (2, 9‐diaminoalkyl substituted 1, 10‐phenanthroline), which binds to the r(CUG) n repeat. Read the full text of the article at10.1002/chem.201602741 . Abstract : " The expanded r(CUG)n repeat is causative of myotonic dystrophy type 1, and small molecules that bind to the expanded r(CUG)n repeat have great potential as therapeutic drugs for incurable diseases ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 14881 ff. (DOI:10.1002/chem.201602741 ).